(NmUZYKA SOWREMENNOST_ (B.s (NSBORNIK STATEJ wYPUSK (B9s - (Na(B.(NaLEKSANDROWs (NREDAKTORs ((NmOSKWAs (NmUZYKAs, 1975)
(No^EREDNOJ DEWQTYJ WYPUSK SBORNIKA mUZYKA I SOWREMENNOST_ POSWQ]ENRAZRABOTKE ISTORIKO(B-(NTEORITI^ESKIH I \STETI^ESKIH PROBLEM MUZYKI hh WEKA(B.s
Keywords: (NISTORIQs